Aggression and sleep: a daylight saving time natural experiment on the effect of mild sleep loss and gain on assaults - Umbach, Rebecca (Journal of experimental criminology, 2017)
The purpose of this study was to test the effect of a mild, short-term sleep loss/gain on assault rates.